2013
DOI: 10.1001/jama.2013.3010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Investigational Vaccine for Preventing Staphylococcus aureus Infections After Cardiothoracic Surgery

Abstract: NFECTIONS WITH STAPHYLOCOCCUS aureus following median sternotomy cause substantial morbidity and mortality. 1-3 A safe vaccine that provides protection against a majority of S aureus strains during the postoperative period would address an important unmet medical need. 4,5 A novel vaccine candidate (V710; Merck Sharp & Dohme Corp) containing the highly conserved S aureus 0657nI iron surface determinant B (IsdB) was protective in animal challenge models 6-8 and immunogenic within 14 days after a single dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
290
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(295 citation statements)
references
References 43 publications
2
290
0
3
Order By: Relevance
“…9 The potential use of this antigen as a component of a vaccine for prevention of S. aureus disease has been previously described. 9,15 However, as a stand-alone vaccine (V710), protection was not observed in a clinical efficacy trial among cardiac surgery patients, 21 despite a significant increase in IsdB antibody titers in the V710 vaccinated patients. Although the IsdB specific with the hospital controls (p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 The potential use of this antigen as a component of a vaccine for prevention of S. aureus disease has been previously described. 9,15 However, as a stand-alone vaccine (V710), protection was not observed in a clinical efficacy trial among cardiac surgery patients, 21 despite a significant increase in IsdB antibody titers in the V710 vaccinated patients. Although the IsdB specific with the hospital controls (p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Although colonization data were not collected in the current study, in the Merck V710 (Protocol 003) trial, nasal colonization data was collected at day of vaccination. 21 Among Protocol 003 patients, it was observed that those who were nasally colonized with S. aureus, had baseline anti-IsdB antibody response was stimulated by V710, it remains unclear which immune mechanisms are critical to mediate clinical efficacy against S. aureus. In recently reported data, protection mediated via IsdB vaccination in mice was dependent on the T-cell (CD4+) response to the vaccine.…”
Section: Hospital S Aureus Cases N = 52mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact clinical results suggests that vaccination with ISdB may have worsened the outcome of S. aureus infection as vaccinated individuals showed significantly higher rate of multi-organ failure. 5 A recent study also suggested a deleterious effect on subsequent S. aureus infection in rabbits vaccinated with a crude surface antigen preparation. 6 These findings reflect the complex nature of S. aureus interactions with the host and challenges facing vaccine development for this pathogen.…”
mentioning
confidence: 98%